Biallelic mutations in LIPT2 cause a mitochondrial lipoylation defect associated with severe neonatal encephalopathy - Habarou, Florence; Haack, Tobias; Nitschke, Patrick; Kölker, Stefan; Korenke, Christoph; Marquardt, Iris (The American journal of human genetics, 2017)
Lipoate serves as a cofactor for the glycine cleavage system (GCS) and four 2-oxoacid dehydrogenases functioning in energy metabolism (α-oxoglutarate dehydrogenase [α-KGDHc] and pyruvate dehydrogenase [PDHc]), or amino acid metabolism (branched-chain oxoacid dehydrogenase, 2-oxoadipate dehydrogenase). Mitochondrial lipoate synthesis involves three enzymatic steps catalyzed sequentially by lipoyl(octanoyl) transferase 2 (LIPT2), lipoic acid synthetase (LIAS), and lipoyltransferase 1 (LIPT1). Mutations in LIAS have been associated with nonketotic hyperglycinemia-like early-onset convulsions and encephalopathy combined with a defect in mitochondrial energy metabolism. LIPT1 deficiency spares GCS deficiency and has been associated with a biochemical signature of combined 2-oxoacid dehydrogenase deficiency leading to early death or Leigh-like encephalopathy. We report on the identification of biallelic LIPT2 mutations in three affected individuals from two families with severe neonatal encephalopathy. Brain MRI showed major cortical atrophy with white matter abnormalities and cysts. Plasma glycine was mildly increased. Affected individuals’ fibroblasts showed reduced oxygen consumption rates, PDHc, α-KGDHc activities, leucine catabolic flux, and decreased protein lipoylation. A normalization of lipoylation was observed after expression of wild-type LIPT2, arguing for LIPT2 requirement in intramitochondrial lipoate synthesis. Lipoic acid supplementation did not improve clinical condition nor activities of PDHc, α-KGDHc, or leucine metabolism in fibroblasts and was ineffective in yeast deleted for the orthologous LIP2.